Digital finance, maize productivity, and welfare of farm households in Burkina Faso - Salimata Traore; Richard K. Moussa (Cogent Economics & Finance)
Maize is a key product entering the consumption basket of households in Burkina Faso and is one of the main crops cultivated in the country. Maize productivity is thus important for food security and household welfare but is constrained by financial issues that can be alleviated by digital finance. Using data from the 2018 Living Standard Measurement Survey (LSMS) of Burkina Faso, we analyze the effects of digital finance uptake on maize productivity and spillover effects on farm households’ welfare. Our results indicate that the adoption of digital finance increases the agricultural productivity of maize producers, and in turn, has a beneficial effect on their welfare. These findings call to emphasize the alleviation of digital finance constraints and policies that aim to improve farmers’ productivity.